Pathways to Wellness: Examining the Educational Impact of the Scout Movement on Junior High School Learners - Samblasinio, Narven G.; Plaza, Rael Christopher O. (Randwick International of Education and Linguistics Science Journal, 2025)
This article investigates the educational and developmental impact of the scouting movement on junior high school learners in the Philippines, with a focus on three institutions: Consuelo National High School, Agusan National High School, and Father Saturnino Urios University. Drawing on a mixed-methods design with 171 participants, the study integrates quantitative data from structured surveys and qualitative insights from focus group discussions with scouting coordinators. Anchored in Youth Development Theory, Social Capital Theory, and Resilience Theory, findings reveal that scouting significantly fosters discipline, self-reliance, civic consciousness, patriotism, and teamwork. The study also uncovers implementation challenges such as resource limitations, insufficient institutional support, and parental concerns. Spearman correlation and multiple regression analysis confirm positive relationships between scouting program strength, stakeholder involvement, training quality, and the development of key student character traits. This article offers insights for educational policymakers and school administrators, recommending enhanced training, inclusive stakeholder participation, and strengthened institutional frameworks to fully realize scouting’s transformative potential in junior education.